2005
DOI: 10.1007/s10494-005-8590-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct Numerical Simulation of a Recirculating, Swirling Flow

Abstract: A direct numerical simulation (DNS) of a recirculating, swirling flow is performed at a Reynolds number of 5000. Detailed one and two point statistics are presented in this paper. Flow visualization and frequency analysis are used to identify a precessing vortex core and to characterize its position, extent and influence on the flow field. The results are compared with laser Doppler velocimetry (LDV) measurements as well as large eddy simulation (LES) data reported in the literature. The present work constitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 16 publications
1
21
0
Order By: Relevance
“…Hence, it is not clear whether the high-order models are more valuable than the KEM. In the last few years, both large eddy simulation (LES) and direct numerical simulation (DNS) have been used by several authors to predict swirling flows [27][28][29]. They have confirmed that the computational results are qualitatively in good agreement with the experimental ones.…”
Section: Introductionmentioning
confidence: 72%
“…Hence, it is not clear whether the high-order models are more valuable than the KEM. In the last few years, both large eddy simulation (LES) and direct numerical simulation (DNS) have been used by several authors to predict swirling flows [27][28][29]. They have confirmed that the computational results are qualitatively in good agreement with the experimental ones.…”
Section: Introductionmentioning
confidence: 72%
“…Although using high-order discretizations or spectral methods is more usual for solving this test case due to its simple geometry, in this research a secondorder scheme is considered as will be explained. Besides very successful DNS computations using second-order schemes (see [38,39]), most of the LES computations are performed based on the low-order discretization methods. Therefore, using this low-order DNS computation can also reveal the performance of this stochastic method in LES simulations without influencing the results by subgrid scale model effects.…”
Section: Reference Homogeneous Shear Flow Simulationmentioning
confidence: 99%
“…Moreover, more recently, direct numerical simulations were used by a few research groups for swirling flow study [14][15][16]. For example, Hu et al [14] investigated temporally 2 Advances in Mechanical Engineering evolving swirling jets with axisymmetric and nonaxisymmetric disturbance.…”
Section: Introductionmentioning
confidence: 99%